Fighting Health Care Provider Stigma: A Novel Approach to Understanding the Impact of Medical School Exposures - Aaron Matthew Brug; Linda M. Nix; Claire B Fitzgerald; Catherine E Jones; Catherine R Counts (Journal of Student-Run Clinics, 2020)
Background: Attitudes of healthcare professionals towards vulnerable patient populations decline throughout their training, and these negative attitudes have been shown to influence health outcomes and access to care. Little is understood about the factors influencing the development of these attitudes. While service-learning has been a proposed solution, there is heterogeneity in curricula, and it is unknown how varying types of exposures affect providers’ stigma towards vulnerable patients.Methods: Allopathic medical students completed a survey assessing attitudes towards four vulnerable patient populations: people who suffer from schizophrenia, people who suffer from major depressive disorder, people experiencing homelessness, and people with a history of intravenous drug use. Students also rated their level of exposure to three conditions (mental illness, homelessness, and addiction or injection drug use) in clinical volunteer, nonclinical volunteer, and observational and personal capacities. Analysis was conducted using Chi-squared tests and linear regression to assess for association(s) between the self-reported exposure(s) and attitudes towards the vulnerable populations.Results: There were 278 survey responses. Clinical and non-clinical volunteer exposures were associated with less stigma towards three of the four patient populations studied. Personal exposures to mental health illnesses as well as addiction or injection drug use were also associated with a reduction in stigma towards vulnerable populations. When controlling for gender, year in school, and race, exposure to persons with a mental illnesses or addiction were each associated with less stigma towards multiple vulnerable populations.Conclusions: Development of curricula for future health care providers should include, if not emphasize, opportunities for students to volunteer in a clinical capacity with vulnerable populations.